The Impact Of Political Dynasties On Community Development In Kediri Regency - Prabowo, Ananditya Bagus; Tambunan, Maria R.U.D (JPAP: Jurnal Penelitian Administrasi Publik, 2024)
Communities are a key aspect of development administration. Due to decentralization, the Regional Government has broader autonomy to run its government independently and is expected to be able to resolve the problems that exist in its region to develop its communities. One of the current issues is political dynasties which have been a longstanding phenomenon in Indonesia, including in the Kediri Regency. Political dynasties consist of elected politicians who have family relatives who have also been elected in current or previous governments. How the leader of the regional government allocates its budget becomes important, especially for the education and health sectors, which have mandatory 20% and 10% from APBD, respectively. This research analyzes the impact of budget allocation for education and health on the community development of the Kediri Regent, with the Human Development Index (HDI) as its value. The method used is descriptive analysis, utilizing secondary data sourced from the Directorate General of Fiscal Balance and the Central Statistics Agency. According to the findings of this study, the allocation of expenditure on education has no substantial impact on the HDI score while expenditure on the health sector has a substantial impact on the HDI score.